Global prevalence and sex differences in rheumatic heart disease: a systematic review and updated meta-analysis - Mutarelli, Antonio; Pantaleao, Alexandre N.; Melo, Pedro H. C.; Nogueira, Wilson; Nogueira, Alleh; Felix, Nicole; Generoso, Giuliano; Cardoso, Rhanderson; Lupieri, Adrien; Aikawa, Elena; Levine, Robert A.; Nunes, Maria C. P. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundRheumatic heart disease (RHD), a sequela of acute rheumatic fever (ARF), remains as the leading cause of acquired cardiac disease in children, posing a significant burden to health systems, especially in low-to-middle-income countries. While ARF shows equal prevalence among sexes in children, clinically manifest RHD in adulthood is strikingly more prevalent in females, with at least a 2:1 ratio. We conducted a meta-analysis to evaluate the global prevalence of RHD and sex disparities alongside risk factors.MethodsPubMed, Embase, Cochrane, and Lilacs were searched for cross-sectional studies on RHD prevalence in individuals aged 5–20, evaluated through echocardiogram-based screening in endemic areas. Studies relying on auscultation were excluded. RHD was defined as borderline/definite by 2012 WHF criteria or possible/probable/definite by WHO criteria.ResultsFifty-eight studies with 215,552 subjects were included. Echo-detected RHD prevalence was 24/1,000 (95%-CI: 20-30) globally. Subgroup analyses showed consistently lower RHD prevalence in males (RR: 0.70; 95%-CI: 0.61–0.80; p < 0.01). Definite RHD prevalence was 9/1,000 (95%-CI: 7–12), with lower rates among males (RR: 0.71; 95%-CI: 0.59–0.86; p < 0.01). Children in private schools (RR: 0.68; 95%-CI: 0.48–0.97; p = 0.03), medium-high-income families (RR: 0.57; 95%-CI: 0.41–0.81; p < 0.01), and urban areas (RR: 0.49; 95%-CI: 0.26–0.93; p = 0.03) exhibited reduced RHD prevalence.ConclusionThis meta-analysis highlights early gender disparities in RHD, with female predominance preceding established valve lesions. Prevalence remains higher in rural areas, public schools, and low-income families, with global prevalence in endemic regions at 24/1,000.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023491941, PROSPERO CRD42023491941.